Restorative rhetoric and ideological positioning in leaders’ social media crisis communication on food security - Nor Azila Hasbullah,; Ramesh Nair,; Isma Noornisa Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2025)
In times of global crisis, leadership discourse plays an important role in shaping public perception and establishing trust. At the intersection of restorative rhetoric and ideological positioning, this study examines how leaders in global food security engaged in social media crisis communication during the COVID-19 pandemic. As the pandemic disrupted food systems and heightened public anxiety, social media emerged as a critical space for leaders to offer reassurance and counter misinformation. This provided a unique opportunity not only to investigate how their discourse functioned to manage the crisis, but also to examine the underlying ideological positioning of these leaders. Drawing on a qualitative research design, tweets from six high-ranking leaders of international food security organisations were analysed by employing a dual analytical framework integrating restorative rhetoric theory with ideological discourse analysis. It was found that the communication of the crisis leaders progressed through five stages of restorative rhetoric, from initial crisis reaction to corrective action and rebuilding. Within these stages, a discourse analysis revealed systematic ideological positioning of leaders as well as the organisations they represented through the use of both semantic structures and formal structures. Leaders consistently emphasised positive institutional attributes while deflecting responsibility. The use of inclusive language served to construct solidarity while maintaining institutional authority. This study uniquely demonstrates that restorative rhetoric in crisis communication is not ideologically neutral, revealing how leaders simultaneously engage in empathetic messaging and strategic legitimacy management, thus contributing to a critical understanding of institutional discourse during global crises.